Т-34. Памятник forever: [повесть : для среднего школьного возраста] / Эдуард Веркин - Веркин Эдуард Николаевич (Серия "Настоящие приключения", 2021)
Экземпляры: ф.23 (20211223) / Инвентарный номер: 61561 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: В 32 / ГРНТИ: 17.82.93 / ББК: 84(2Рос=Рус)6-44